QUALITY IMPROVEMENT PROJECT: DETECTING, INSTIGATING AND ASSESSING EFFECTIVE HANDOVER TECHNIQUES. Issue 11 (9th October 2013) - Warrell, Clare; Doshi, Anisha; Mayhew, Joseph; Thacker, Eve; McColgan, Peter; Yates, Timothy; Rohrer, Jonathan; Ingle, Gordon
Abstract : Safe handover is integral to patient safety. Since the implementation of the European Working Time Regulations, doctors' working patterns have largely moved to a full shift system. Consequently, there is now greater need for numerous thorough handovers between medical teams. According to the Royal College of Physicians report, poor handover between doctors is a common cause of error in hospitals, and is a major preventable cause of patient harm. Therefore, a number of initiatives have been devised by the Royal College of Physicians and British Medical Association over the last two years in an attempt to standardise the system to reduce errors. 1 2 As Junior doctors we recognised that our medical team weekend handover system was an area needing improvement. The Weekend doctor had to collate handover information from multiple emails which was time consuming and tedious. The Quality Improvement team aimed to optimise staff efficiency by improving the weekend handover system by; enabling easy assimilation and identification of patients requiring on–call SpR and SHO review, creating a standardised word document template for handover saved onto a shared network drive accessible to all doctors, evaluating the effectiveness of the new template by assessing perceptions of the new system prior to and after it was introduced. We developed an anonymised online questionnaire for senior house officers and specialist registrars. Questions included; the time taken to collate the weekend list, their confidence in the completeness of the handover, how appropriate the jobs requested were. The questionnaire was carried out pre–and post–instigation of the new template. We analysed this information using graphical represention of the Likert scale data on doctors attitudes to the new template (see Figure 1). All but one doctor felt that the previous weekend handover method needed improving. All clinicians felt the weekend handover we introduced was better than the pre–existing system. SHO time spent on amalgamating the weekend list was reduced on average by 1 hour. Doctor's impressions before implementation of the handover template ranged from 'very difficult' to 'average'. Afterwards a majority felt it was 'easy.' We have responded to feedback to optimise the template. There are plans to extend this template system to weekday handovers. We also aim to create a better forum with registrars for verbal weekend handover. We plan to assess measurable qualitative outcomes of these changes before and after their implementation, to ensure that they are sustainable and serve their purpose. This quality improvement project has shown that the introduction of a simple template has increased the efficiency and confidence of doctors in the weekend handover of patients at our hospital. The team learnt the importance of acting upon, rather than tolerating inefficient systems in health provision.